A STABILITY STUDY OF AYURVEDIC LAXATIVE FORMULATION - CONSTAC GRANULATION - Mohanrao More, *Akash; Jagtap, Priyanka; Bhagwat Kulkarni, Bhushan (International Journal of Ayurveda and Pharma Research, 2015)
Nowadays herbal medicines are accepted all over the world. The major weakness is consistency in the quality of the product over a range of time. So stability testing is necessary to ensure the quality of herbal products which is an evidence for the quality of the finished product. The present study was conducted to evaluate accelerated stability (Temperature: 40 °C ± 2, Relative Humidity (RH): 75% ± 5) and real time stability (Temperature: 25 °C ± 2, Relative Humidity (RH): 60% ± 5) of Constac granulation. A study was conducted as per ICH guideline Q1A (R2). The variation in the organoleptic, physico-chemical and microbial load constants of the Constac granulation (fine granulation) was observed during 0 (initial), 1st, 3rd and 6th month. Results of different physico-chemical parameters were taken into consideration to evaluate intercept and slope. It was found that there was no change in color, odour and taste of Constac granulation up to storage of 6 months at accelerated condition. Constac granulation was suitable at accelerated condition up to 6month storage. It can be extrapolated that shelf life of Constac granulation is 23.02 months. The real time stability data of Constac granulation showed very good stability up to 1 year.